Comparison of nitrous oxide (N2O) analyzers for high-precision measurements of atmospheric mole fractions - Lebegue, Benjamin; Schmidt, Martina; Ramonet, Michel; Wastine, Benoit; Yver Kwok, Camille; Laurent, Olivier; Belviso, Sauveur; Guemri, Ali; Philippon, Carole; Smith, Jeremiah; Conil, Sebastien (Atmospheric measurement techniques, 2016)
Abstract. Over the last few decades, in situ measurements of atmospheric N2O mole fractions have been performed using gas chromatographs (GCs) equipped with electron capture detectors. This technique, however, becomes very challenging when trying to detect the small variations of N2O as the detectors are highly nonlinear and the GCs at remote stations require a considerable amount of maintenance by qualified technicians to maintain good short-term and long-term repeatability. With new robust optical spectrometers now available for N2O measurements, we aim to identify a robust and stable analyzer that can be integrated into atmospheric monitoring networks, such as the Integrated Carbon Observation System (ICOS). In this study, we present the most complete comparison of N2O analyzers, with seven analyzers that were developed and commercialized by five different companies. Each instrument was characterized during a time period of approximately 8 weeks. The test protocols included the characterization of the short-term and long-term repeatability, drift, temperature dependence, linearity and sensitivity to water vapor. During the test period, ambient air measurements were compared under field conditions at the Gif-sur-Yvette station. All of the analyzers showed a standard deviation better than 0.1 ppb for the 10 min averages. Some analyzers would benefit from improvements in temperature stability to reduce the instrument drift, which could then help in reducing the frequency of calibrations. For most instruments, the water vapor correction algorithms applied by companies are not sufficient for high-precision atmospheric measurements, which results in the need to dry the ambient air prior to analysis.